Upaya Meningkatkan Daya Ingat Tentang Materi Keseimbangan Lingkungan Dengan Menerapkan Teknik Mind Mapping - Siti Rochanah (Journal on Education, 2021)
This study aims to determine whether nor not there is an increase in the memory of the Environmental Balance material through the application of Mind Mapping techniques to students of Class 4-C SD Negeri Kendangsari I/276 Surabaya, and to determine how much the increase in the memory of the Environmental Balance material through the application of Mind Mapping techniques to students. Class 4-C SD Negeri Kendangsari I/276 Surabaya. This research was conducted to overcome the problem of low memory experienced by students of Class 4-C SD Negeri Kendangsari I/276 Surabaya. Therefore, the author as a teacher in the class tries to apply the Mind Mapping technique which focuses on student learning activities in order to get educational values, knowledge in learning and maximum memory. The action research was carried out in two learning cycles and, based on the exposure to the results of the research and discussion, it can be concluded that there is an increase in the memory of the Environmental Balance material through the application of Mind Mapping techniques in Class 4-C students of SD Negeri Kendangsari I/276 Surabaya. Improved memory of Environmental Balance material through the application of Mind Mapping techniques in Grade 4-C students of SD Negeri Kendangsari I/276 Surabaya an average of 25%